Endothelial progenitor cells in regeneration after acute lung injury - Rafat, Neysan; Tönshoff, Burkhard; Bierhaus, Angelika; Beck, Grietje (American journal of respiratory cell and molecular biology, 2013)
Acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) are common disorders in patients requiring critical care. The clinical management of these disorders is difficult and unrewarding, and thus they are among the most common causes of death in intensive care units. The activation and damage of pulmonary endothelium comprise the hallmark of ALI/ARDS. Therefore, the recruitment of circulating endothelial progenitor cells (EPCs) to these lesions may exert a beneficial effect on the clinical course of ALI/ARDS. Consequently, cell-based therapies using stem cells to regenerate lung tissue have emerged as potential novel treatment strategies. Although initial studies suggested implantations of exogenously administered bone marrow-derived progenitor cells into damaged vessel walls, recent evidence indicates that this is rather a rare occurrence with uncertain physiologic significance. In the past few years, different populations of progenitor cells were identified, with different functional capacities. This review (1) highlights the different populations of EPCs identified or administered in different models of ALI/ARDS, (2) reports on whether beneficial effects of EPCs could be demonstrated, and (3) puts the conflicting results of different studies into perspective.